2019
DOI: 10.1038/s41598-019-40217-1
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Conformation of the Influenza B Virus M2 Protein in Lipid Bilayers

Abstract: Influenza A and B viruses cause seasonal flu epidemics. The M2 protein of influenza B (BM2) is a membrane-embedded tetrameric proton channel that is essential for the viral lifecycle. BM2 is a functional analog of AM2 but shares only 24% sequence identity for the transmembrane (TM) domain. The structure and function of AM2, which is targeted by two antiviral drugs, have been well characterized. In comparison, much less is known about the structure of BM2 and no drug is so far available to inhibit this protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 75 publications
5
16
0
Order By: Relevance
“…5 ) show very similar chemical shifts for the TM residues in the POPE and POPC : POPG membranes, indicating that the TM helix conformation is unaffected by the membrane curvature. This observation is consistent with the invariance of BM2 chemical shifts between DLPE and POPC : POPG membranes at high pH 29 . Because the cytoplasmic domain forms a β-strand at low pH but is disordered at high pH, the membrane curvature is correlated with the β-strand conformation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…5 ) show very similar chemical shifts for the TM residues in the POPE and POPC : POPG membranes, indicating that the TM helix conformation is unaffected by the membrane curvature. This observation is consistent with the invariance of BM2 chemical shifts between DLPE and POPC : POPG membranes at high pH 29 . Because the cytoplasmic domain forms a β-strand at low pH but is disordered at high pH, the membrane curvature is correlated with the β-strand conformation.…”
Section: Resultssupporting
confidence: 90%
“…1b – c , Extended Data Figs. 2 and 3 ), following previous assignment of a similar construct 29 . We utilized sequential and medium-range cross peaks ( i to i +1 or i +2) in the 3D NCCX and 3D CCC spectra to facilitate assignment of overlapping peaks.…”
Section: Resultsmentioning
confidence: 98%
“…Microcrystalline GB1 samples were expressed and purified as previously described [35][36] . Glucagon peptide was purchased from Biopeptek Pharmaceuticals (Malvern, PA) and fibrillized in pH 2 solution at 21˚C for 7 days at a concentration of 8 mg/ml 37 .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies demonstrated that transmembrane proteins spontaneously fold while incorporated in an artificial lipid membrane. This behavior is utilized in analytical applications such as circular dichroism (CD) spectroscopy and solution nuclear magnetic resonance (NMR) studies (Engelman and Steitz, 1981;Ladokhin et al, 2010;Mandala et al, 2019). In order to aid NCL multiple surfactants were investigated to increase the solubility of transmembrane peptides in guanidinium chloride or urea as additives to ligation buffer.…”
Section: External Conditionsmentioning
confidence: 99%